Waist Circumference and Waist-to-Height Ratio as Indicators for Excess Adiposity in Adolescents - Mulyasari, Indri; Pontang, Galeh Septiar (Jurnal Gizi dan Pangan, 2018)
The aimed of study was to evaluate the accuracy of Waist Circumference (WC) and Waist-to-Height Ratio (WHtR) for identification of excess adiposity in adolescents. The study design was diagnostic study. The subjects consisted of 620 adolescents (283 boys and 337 girls) aged 14-18 years. The classification of excess adiposity termed as overfat and obese was based on age-and sex-specific percent body fat cut-off values of body fat reference curves for children from the Growth Foundation. Receiver-operating characteristic (ROC) curve analyses was used to assess the accuracy of WC and WHtR as diagnostic tests of excess adiposity in adolescent. Area under curve (AUC) of WC and WHtR for the diagnostic of overfat were over 0.8 for boys and over 0.9 for girls. Whereas for obese, the AUC of WC and WHtR were over 0.9 for both sexes. The thresholds for defining overfat were 75.25 cm for WC and 0.45 for WHtR (Sensitivity (Se) and Specificity (Sp) >0.8) for boys, and 73.85 cm for WC and 0.49 for WHtR (Se dan Sp >0.8) for girls. The thresholds for defining obese were 86.45 cm for WC and 0.51 for WHtR (Se=1; Sp>0.9) for boys, and 75.60 cm for WC (Se and Sp >0.8) and 0.55 for WHtR (Se>0.8; Sp >0.9) for girls. WC and WHtR are accurate for screening of excess adiposity in adolescents.